Pelatihan Tukang GMIT Jemaat Eklesia, Desa Daurendale, Landuleko, Klasis Rote Timur - Krisantos Ria Bela; Sri Santi L. M. F. Seran; Gregorius Paus Usboko; Mauritius I. R. Naikofi; Budhi Benyamin Lily; Jeremias Gelu Plewang (CV. Gio Architect, 2023)
The Eklesia Mokdale Church located in East Rote Village suffered significant damage during the Seroja tropical cyclone. This church is the result of self-help which was also built independently by the people in the village. Even though quite a lot of men who live their work as builders, it turns out that there are still many who do not understand the concepts and steps for making buildings that are structurally strong, against earthquakes and strong winds. With this training, it is hoped that the community will understand and be able to build structurally strong buildings against earthquakes and strong winds.